Information Use Behaviour of Engineering Students: A Case Study - Subhash Reddy, B.; Krishnamurthy, M. (Journal of Information and Knowledge, 2018)
Study of information use is an important aspect of understanding the end users’ behaviour. This study is aimed at understanding the information use behavior of postgraduate engineering students in an institute of technology. The data for this study was collected through an online survey of 130 postgraduate engineering students belonging to various disciplines. The study reveals the frequency of library visit, the purpose of visiting the library, types of facilities, services and library resources used by the students. Data on strategy for searching documents sources, user’s opinion, and user satisfaction with print and e-resources were also collected. The study shows that most of the students are satisfied with library facilities.